FAKTORS ASSOCIATED WITH THE INCIDENCE OF PREECLAMPSIA IN PREGNANT WOMEN AT RSUP. DR. M. DJAMIL PADANG IN 2022 - Dewi, Nur Cintia; Abdiana , Abdiana; Fitrayeni , Fitrayeni (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Preeclampsia still a complication of pregnancy is in need of special attention if not to be overcome by directly resulting in an increase in the number of deaths of pregnant women. The factors that can cause preeclampsia for pregnant women among them are age, parity, and the nutritional status of mothers. This research seeks to capture that deals with incident preeclampsia for pregnant women at RSUP Dr. M. Djamil Padang of 2022. Method: This research is quantitative research with an observational analytical design because there is no treatment of the objects studied. The research design used was cross sectional, that is, measurements and observations were carried out only once at a time. Result: The result showed 64,3 % preeclampsia pregnant women with heavy. This research result indicates the majority of pregnant women with a heavy risk preeklampsia 60,5 % ( p = 0,046; OR = 2,263; CI 95% = 1,081-4,736 ), the parity of risky 56,6 % ( p = 0,040; OR = 2,297; CI 95 % = 1,101-1,790 ) and nutritional status of risky 67,4 % ( p = 0,011; OR = 2,888; CI 95 % = 1,341-6,215) 95. Conclusion: It's concluded that there's an age relationship, parity and nutrition status of pregnant mothers against preeclampsia. Advice for health officials is particularly midwifes to increase counseling and socialization regarding pregnancy complications and raise caution to patients who are at risk of preeclampsia.